All You Need is Love. Issue 2 (April 2015) - Hartwig, Mervyn
Abstract : This essay sets out some key qualities of love according to the philosophy of critical realism, together with Roy Bhaskar's arguments for them. It then considers how Bhaskar's claims stack up with the findings of modern physics, indicates how the category of love unifies the philosophical system of critical realism and critiques Luc Ferry's view that the reign of love has already begun in the West, before briefly discussing the practical application of Bhaskar's philosophy of love in the work of feminist critical realist social theorist Lena Gunnarsson.